The Protein Kinase Cdr2, Related to Nim1/Cdr1 Mitotic Inducer, Regulates the Onset of Mitosis in Fission Yeast - Kanoh, Junko; Russell, Paul (Molecular biology of the cell, 1998)
Cdc2–Cyclin B, the protein kinase that catalyzes the onset of mitosis, is subject to multiple forms of regulation. In the fission yeast Schizosaccharomyces pombe and most other species, a key mode of Cdc2–Cyclin B regulation is the inhibitory phosphorylation of Cdc2 on tyrosine-15. This phosphorylation is catalyzed by the protein kinases Wee1 and Mik1 and removed by the phosphatase Cdc25. These proteins are also regulated, a notable example being the inhibition of Wee1 by the protein kinase Nim1/Cdr1. The temperature-sensitive mutation cdc25–22 is synthetic lethal with nim1/cdr1 mutations, suggesting that a synthetic lethal genetic screen could be used to identify novel mitotic regulators. Here we describe that such a screen has identifiedcdr2 + , a gene that has an important role in the mitotic control. Cdr2 is a 775 amino acid protein kinase that is closely related to Nim1 and mitotic control proteins in budding yeast. Deletion of cdr2 causes a G2-M delay that is more severe than that caused by nim1/cdr1 mutations. Genetic studies are consistent with a model in which Cdr2 negatively regulates Wee1. This model is supported by experiments showing that Cdr2 associates with the N-terminal regulatory domain of Wee1 in cell lysates and phosphorylates Wee1 in vitro. Thus, Cdr2 is a novel mitotic control protein that appears to regulate Wee1.